2021
DOI: 10.1128/msphere.00986-20
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus UL7, miR-US5-1, and miR-UL112-3p Inactivation of FOXO3a Protects CD34 + Hematopoietic Progenitor Cells from Apoptosis

Abstract: Human cytomegalovirus (HCMV) infection of myeloid lineage cells, such as CD34+ hematopoietic progenitor cells (HPCs) or monocytes, results in the upregulation of antiapoptotic cellular proteins that protect the newly infected cells from programmed cell death. The mechanisms used by HCMV to regulate proapoptotic cellular proteins upon infection of CD34+ HPCs have not been fully explored. Here, we show that HCMV utilizes pUL7, a secreted protein that signals through the FLT3 receptor, and miR-US5-1 and miR-UL112… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Additional studies performed in the absence of infection or using cell lines that are not permissive for HCMV latency have suggested that HCMV miRNAs can inhibit apoptosis through suppression of SLC25A6/ANT3 [75] and immediate early gene X-1 (IEX1) [76]. More recently, HCMV miR-US5-1 and miR-UL112-3p were shown to target FOXO3a [77], a member of the mammalian Forkhead Box O family of transcription factors that promotes mitochondrial-dependent and -independent mechanisms of apoptosis induction [78,79]. FOXO3a binds to the promoters of pro-apoptotic regulators such as Bcl-2-like protein 11 (Bim) and stimulates its expression [80].…”
Section: Hcmv Mirnas Involved In Latency Establishment and Maintenancementioning
confidence: 99%
See 4 more Smart Citations
“…Additional studies performed in the absence of infection or using cell lines that are not permissive for HCMV latency have suggested that HCMV miRNAs can inhibit apoptosis through suppression of SLC25A6/ANT3 [75] and immediate early gene X-1 (IEX1) [76]. More recently, HCMV miR-US5-1 and miR-UL112-3p were shown to target FOXO3a [77], a member of the mammalian Forkhead Box O family of transcription factors that promotes mitochondrial-dependent and -independent mechanisms of apoptosis induction [78,79]. FOXO3a binds to the promoters of pro-apoptotic regulators such as Bcl-2-like protein 11 (Bim) and stimulates its expression [80].…”
Section: Hcmv Mirnas Involved In Latency Establishment and Maintenancementioning
confidence: 99%
“…The activity of FOXO3a is regulated by PI3K/AKT and MEK/ERK signaling, which mediate phosphorylation and translocation of FOXO3a to the cytoplasm [81][82][83]. The FOXO3a transcript is downregulated by HCMV miR-US5-1 and miR-UL112-3p and the protein is targeted for phosphorylation and inactivation by the HCMV FLT3L homolog UL7 [77]. Both the miRNAs and UL7 are expressed at early times post-infection of CD34 + HPC [15,77] and reduce FOXO3a levels and activity to limit the induction of apoptosis [77] in this cell type ( Figure 2).…”
Section: Hcmv Mirnas Involved In Latency Establishment and Maintenancementioning
confidence: 99%
See 3 more Smart Citations